Comparative cost-benefit analysis of energy efficient lighting in retrofit buildings - Liow, Shii Yin (2022)
Lighting retrofits aim to reduce energy consumption and environmental impact while providing better lighting quality. Challenges in retrofitting include the retrofit method and the economic feasibility assessment before actual implementation. This research is aimed to study the lighting quality, economic and environmental benefits of retrofitting the existing conventional lighting with energy-efficient lighting in a high-rise building. In the preliminary study, three cases with different light sources in compliance with MS 1525, SIRIM and JKR standards were modelled to study lighting qualities such as illuminance level, uniformity and lighting power intensity. The results showed that energy-efficient lighting and good lighting quality are compatible. Several factors need to be considered when selecting the LED for retrofitting, including luminous flux and polar curve. In the comprehensive study, five cases with different degrees of LED retrofitting were modelled compliant with the standards to study the energy efficiency and cost-effectiveness. The findings showed that retrofitting using a higher percentage of LEDs gives more savings in terms of life cycle cost, electricity consumption and CO2 emission. Retrofitting with 100% LEDs can provide up to 20% net saving and save up to 34.7% in electricity consumption and CO2 emissions per year. In cases where lighting systems are not 100% retrofitted with LEDs, priority is given to replacing longer-running inefficient light sources to maximize the net saving. By retrofitting from the long operating hours to the short operating hours, the net saving can achieve 6.7% to 8.4% higher than vice versa. Moreover, retrofitting using a longer lifespan LED should consider first because it results in more net saving, and the net saving of a 50,000-hour-life LED system can be as high as 20%. The sensitivity analyses showed that the change in LED prices is unlikely to negate the net saving of the retrofit systems. When the discount rate increases by 20% and the electricity tariff reduce by 45%, the lower percentage of LED retrofit becomes more preferred than the higher percentage of LED retrofit